Realising the Right to Dignity of Zimbabwean Migrant Women in Botswana: A Practical Approach (African Human Mobility Review, 2023)
This article delves into the multifaceted human rights challenges confronting migrant women in Botswana, with a particular focus on women from Zimbabwe. The exploration reveals pervasive gender-specific barriers hampering these women’s access to essential healthcare and decent employment opportunities. Additionally, it sheds light on their heightened susceptibility to gender-based violence, exploitation, and discriminatory practices in the workplace, all of which collectively infringe upon their fundamental right to dignity. Central to the argument is the imperative to safeguard and uphold the right to dignity for Zimbabwean migrant women. This necessitates the establishment of an environment that not only guarantees access to basic human needs but also fosters a space free from fear and abuse. The article advocates for the implementation of a “Migration with Dignity Framework” in Botswana. This proposed framework emphasizes the critical importance of gender-sensitive policies, robust access to justice mechanisms, non-discrimination initiatives, and the assurance of healthcare, secure working conditions, and adequate housing.